2023
DOI: 10.3390/coatings13091649
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water-Based Primer Pretreatment on the Performance of Water-Based Inkjet Coatings on Wood Surfaces

Ruijuan Sang,
Fei Yang,
Zhenxian Fan

Abstract: Wood surface staining suffers from volatile organic gas (VOC) emissions and uneven staining at knots, and these environmental and decorative performance issues are the main restrictions in the application of wood products, indoors and outdoors. Herein, the method of wood-based panel surface staining is presented for improving environmental and decorative performance using environmentally friendly water-based inks, water-based primers, and digital inkjet coloring technology. The wood-based panels’ dye coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The first is functional design, which involves determining the intended function of furniture and identifying the primary benefits it is expected to provide (Figure 1) [1]. Aesthetic design, on the other hand, focuses on the artistic aspects of furniture design, encompassing features such as form, texture, color, and shape, while taking into consideration the influence of relevant cultures or fashion trends, as well as the demands of consumers [2][3][4][5]. Engineering design, which is the last key element of design, is the process of determining the most appropriate ergonomic criteria, materials, construction techniques, and manufacturing technologies [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The first is functional design, which involves determining the intended function of furniture and identifying the primary benefits it is expected to provide (Figure 1) [1]. Aesthetic design, on the other hand, focuses on the artistic aspects of furniture design, encompassing features such as form, texture, color, and shape, while taking into consideration the influence of relevant cultures or fashion trends, as well as the demands of consumers [2][3][4][5]. Engineering design, which is the last key element of design, is the process of determining the most appropriate ergonomic criteria, materials, construction techniques, and manufacturing technologies [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the UV inkjet technology [17] requires a white background substrate to match the conventional colors, and there is an adhesion issue with conventional top coating used as a base for direct inkjet printing [18]. Therefore, the primer-treated substrate can improve the mechanical properties and printing quality of the paint film [19]. However, research on water-based primer [20,21] printing systems for wood applications is still limited, and research on the coloring performance of wood product coatings needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…CaCO 3 is characterized by low cost, abundant reserves, high stability, and permeability, making it suitable for industrial use that requires mass production [22][23][24][25]. In addition, field research found that oak planks [19] are commonly used in the floor production line of solid wood materials. Their texture is firm, and they have beautiful grain, but part of the surface of the oak boards has scars, scratches, stains, and other defect phenomena.…”
Section: Introductionmentioning
confidence: 99%